2017
DOI: 10.1186/s12889-017-4159-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors of home delivery among women in Northern Ethiopia: a case control study

Abstract: BackgroundMaternal mortality remains a major challenge to health systems worldwide. Although most pregnancies and births are uneventful, approximately 15% of all pregnant women develop potentially life-threatening complications. Home delivery in this context can be acutely threatening, particularly in developing countries where emergency care and transportation are less available. This study identifies factors associated with home delivery in Tanqua-Abergele District, Tigray, northern Ethiopia.MethodsUnmatched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 11 publications
(21 reference statements)
8
48
0
Order By: Relevance
“…Studies have shown that mothers' socio‐demographic characteristics, such as educational status, occupation, and residential area, influence their choice of place of delivery . In different contexts, it has been shown that the educational status of the pregnant woman does influence the woman's perception of home delivery and health seeking behaviour . Kitui et al analysed the 2008/2009 Kenya DHS data and demonstrated that women who were more educated, lived in urban residence, and had lower parity were less likely to deliver at home .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that mothers' socio‐demographic characteristics, such as educational status, occupation, and residential area, influence their choice of place of delivery . In different contexts, it has been shown that the educational status of the pregnant woman does influence the woman's perception of home delivery and health seeking behaviour . Kitui et al analysed the 2008/2009 Kenya DHS data and demonstrated that women who were more educated, lived in urban residence, and had lower parity were less likely to deliver at home .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In different contexts, it has been shown that the educational status of the pregnant woman does influence the woman's perception of home delivery and health seeking behaviour. [18][19][20][21] Kitui et al analysed the 2008/2009 Kenya DHS data and demonstrated that women who were more educated, lived in urban residence, and had lower parity were less likely to deliver at home. 22 Also, women who are Muslims were more likely to deliver at home compared with other religions.…”
mentioning
confidence: 99%
“…In Eastern and Southern Africa, about 38% deliveries occurred at home [2]. In Ethiopia, community based surveys conducted in various regions of the country reported the magnitude of home deliveries to range from 31% to 96% [5][6][7][8][9][10][11][12]. Similarly, according to the Ethiopian Demographic Health Survey (EDHS) 2016, the prevalence of home delivery was reported to be 73% [3].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of home delivery is attributed to many factors. Among these are low socioeconomic status [9][10][11][12][13][14][15][16], women illiteracy, lack of pregnancy monitoring, inaccessibility of health facilities [17][18][19][20][21][22][23][24] and women's position in the society [25][26][27][28][29][30][31][32], which confers little decision-making power. Accurate epidemiological information is necessary to understand the magnitude home delivery among women of child bearing age, to guide interventions that helps to improve institutional delivery and improve women's wellbeing and to monitor trends over time.Thus,the aim of this study was to assess the magnitude of home delivery and associated factors among women of child bearing age in Sherkole district, Western Ethiopia.…”
Section: Introductionmentioning
confidence: 99%